Constructive Dual Methods for Nonlinear Discrete Programming Problems - Bárcia, Paulo (2019)
This paper is primarily concerned with the extension of the bound improving sequence algorithm (Bárcia, 1985, 1987) to nonlinear discrete programming problems. Our attention is then focused to quadratic constrained binary problems. It is shown that for a particular class of these problems a computationally efficient algorithm is derived from the general approach.